The value relevance f the operacional leases - Pais, C. (39th European Accounting Association, 2016)
The operational leases is accounted as an expense and not as an asset but there is a proposal by the International Accounting Standards Board (IASB) to accounting the operational leases as a finance lease because IASB believes that that improves the quality and comparability. I test whether the accounting of an operational lease as a finance lease is more value relevant to investors, whether this has changed over time and whether the operating lease liabilities is perceived differently of the operating lease assets by the investor. My results suggest, for the largest European firms, that the investor incorporates the information of operating leases on the share price but I do not conclude that there is a change of that over time; however the operating lease liability is perceived differently of the operating lease asset. These results confirm that the accounting of the operational leases as a finance lease provides information which is much more useful.